2020
DOI: 10.3390/mi11070632
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Evaluation of a Multi-Site Clinical Depth Recording Electrode for Monitoring Cerebral Tissue Oxygen

Abstract: The intracranial measurement of local cerebral tissue oxygen levels—PbtO2—has become a useful tool for the critical care unit to investigate severe trauma and ischemia injury in patients. Our preliminary work in animal models supports the hypothesis that multi-site depth electrode recording of PbtO2 may give surgeons and critical care providers needed information about brain viability and the capacity for better recovery. Here, we present a surface morphology characterization and an electrochemical eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In fact, in the neurocritical field, this type of probes has been coupled to intracranial pressure monitoring allowing continuous PO 2 recording in the human brain. In addition, a recent in vitro study suggested that this probe may allow multisite electrophysiology and standardized electrochemical detection of O 2 , which is promising in multimodal monitoring [18].…”
Section: Oxygen and Carbon Dioxide Measurementsmentioning
confidence: 99%
“…In fact, in the neurocritical field, this type of probes has been coupled to intracranial pressure monitoring allowing continuous PO 2 recording in the human brain. In addition, a recent in vitro study suggested that this probe may allow multisite electrophysiology and standardized electrochemical detection of O 2 , which is promising in multimodal monitoring [18].…”
Section: Oxygen and Carbon Dioxide Measurementsmentioning
confidence: 99%
“…408 Thus, PbtO 2 is treated as a reliable marker of CBF and cerebral ischemia under certain conditions. The current clinical methods used to monitor PbtO 2 include invasive techniques such as Clark electrode-based electrochemical sensing and fluorescence quenching-based optical sensing [ 49 ], also the non-invasive techniques like NIRS [ 426 , 427 ]. The basic device of an electrochemical PO 2 sensor designed for medicine was first proposed by Leland Clark in 1956 [ 106 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Among those, the amperometric sensing technique allows real-time monitoring of brain oxygenation and can be an effective bedside method for the detection of cerebral ischemia. Due to the electrocatalytic behavior of Pt, Ledo et al reported the potential application of those commercially available intracranial recording electrodes that include a thin Pt film on their recording sites, for amperometric monitoring of PbtO 2 [ 5 ]. They conducted a surface morphology characterization and an electrochemical evaluation of the performance of such a device for oxygen detection and concluded that these probes can be repurposed for in vivo multisite monitoring of PbtO 2 .…”
Section: Application Demonstrationmentioning
confidence: 99%
“…In this editorial note, we briefly review the major findings of the 10 articles published in the Special Issue on microelectrode arrays and application to medical devices. The articles are categorized into three sections, i.e., fabrication techniques [ 1 , 2 , 3 , 4 ], application demonstration [ 5 , 6 , 7 , 8 ], and review of recent advances in this field [ 9 , 10 ].…”
mentioning
confidence: 99%